Pengaruh Model Picture and Picture terhadap Literasi Menulis Puisi Siswa Kelas VII SMP Negeri 1 Bakam - Nelsi Utami; Liza Murniviyanti; Manunah Manunah (Pusat riset dan Inovasi Nasional, 2025)
his study aims to find out that there is no influence of the Picture and picture model on the poetry writing literacy of grade VII students of SMP Negeri 1 Bakam. This research includes experimental research using Quasi Experimental Design in the form of Nonequivalent Control Group Design. The population in this study is all grade VII of SMP Negeri 1 Bakam. The sample was drawn using a total sampling technique of 48 students. The process applied during this study is to use the picture and picture model in teaching poetry material. The data collection technique uses pretest and posttest writing poetry. The analysis technique used in this study is the t-test. Based on the sig value of 0.000 which means less than 0.05 so H0 is rejected. Thus, there is an influence of the Picture and picture model on the poetry writing literacy of grade VII students of SMP Negeri 1 Bakam.